CIRI-CIRI ADVERBIA BAHASA MELAYU JAMBI DI KELURAHAN TANJUNG RADEN KECAMATAN DANAU TELUK KOTA JAMBI (KAJIAN MORFOSINTAKSIS) - Sainil Amral; Retno Wahyu Ningsih (Universitas Batanghari, 2019)
This research aims to describe adverbial of Jambi Malay language in Tanjung Raden districk Danau Teluk subdistrict Jambi city. This research uses qualitative descriptive methods. The data is collected through observation and interview. In this study, the data is in the form of Adverbs which are derived from 6 informants. The sample is natice speaker of Jambi Malay language in Tanjung Raden districk Danau Teluk subdistrict Jambi city. The data are analyzed by using method of distribution analysis. The results of this research show that the characteristic of Jambi Malay language adverbs include; the characteristic of morphological adverbc which can be seen from the words ‘konyok’ which means not because that word does not indicate a hallmark of a word that is undergoing of morphological process or cannot join the affix particle. Meanwhile the characteristic of syntactical adverb can be seen from the word ‘be’ which means ‘just’. From the position of the structure, it can be concluded that the attitude of adverb (b) always follows the word that is explained.